2018
DOI: 10.1002/jcp.27798
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Nutlin‐3 on morphology, cellular proliferation, and apoptosis in rat primary mesenchymal stem cells

Abstract: Introduction Nutlin‐3 is a powerful antagonist of murine double minute 2/p53 interaction demonstrating promising therapeutic anticancer activity, which has not been clinically approved yet. Mesenchymal stem cells (MSCs) are an important part of the bone marrow niche and support regeneration and proliferation of hematopoietic stem cells after exposure to myelotoxic anticancer agents; however, the effect of Nutlin‐3 compounds on MSCs themselves remains to be elucidated. Materials and Methods Rat‐derived bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These cells were found to be relatively resistant to nutlin-3 in rats 33 and human BMSCs. These cells were found to be relatively resistant to nutlin-3 in rats 33 and human BMSCs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These cells were found to be relatively resistant to nutlin-3 in rats 33 and human BMSCs. These cells were found to be relatively resistant to nutlin-3 in rats 33 and human BMSCs.…”
Section: Discussionmentioning
confidence: 98%
“…[9][10][11][12][13][14] Moreover, research suggests that nutlin-3 induces apoptosis and suppresses cell growth in the absence of wild-type TP53 through the TP53 homolog of p73, 15,16 and sensitizes TP53-defective cancer cells to different anticancer agents, such as arsenic trioxide, 17 radiation, 18 and doxorubicin. 33 The present research seeks to investigate the effectiveness of nutlin-3 in the proliferation and survival of MSCs obtained from human bone marrow (BMSCs). 20 Preclinical studies found nutlin-3 to present treatment potential for human cancer cells with wild-type TP53.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mdm2 has been demonstrated to play a major role in regulating hematopoietic stem cell survival [57]. Moreover, previous studies have shown that Mdm2 inhibitors can inhibit cell proliferation in rBM-MSCs and hBM-MSCs [20, 21]. Dysfunction of the Mdm2/p53 axis has been linked to cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, p53 is kept at low levels by murine double minute 2 (Mdm2), which can bind to p53 and act as p53 ubiquitin ligase that negatively regulates p53 function in several cellular pathways, such as cell cycle and apoptosis. Previous studies have shown that the Mdm2 inhibitor can decrease cell proliferation in rat BM-MSCs (rBM-MSCs) and hBM-MSCs [20, 21]. However, the mechanism underlying PAME-induced p53 stabilization and consequent cell cycle arrest in hBM-MSCs has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%